“Dakwah Pembebasan” Perspektif KH. MA. Sahal Mahfudh Dalam Buku “Nuansa Fiqih Sosial” - Muhammad Ahnu Idris; Taufik Taufik; Bahrur Rosi (LP2M IAI Miftahul Ulum Pamekasan, 2020)
This article discusses the thoughts of da'wah bi al-hâl KH. MA Sahal Mahfudh in his book entitled